Egyptian electronic government: The university enrolment case study - Hassan, H. S. H.; Shehab, Essam; Peppard, Joe (Cranfield University, 2010)
E-government projects have potential for greaterefficiency and effectiveness of government operations. For thisreason, many developing countries governments have investedheavily in this agenda and an increasing number of e- governmentprojects are being implemented. However, there is a lack of clearcase material, which describes the potentialities and consequenceexperienced by organizations trying to manage with this change. TheMinistry of State for Administrative Development (MSAD) is theorganization responsible for the e- Government program in Egyptsince early 2004. This paper presents a case study of the process ofadmission to public universities and institutions in Egypt which is ledby MSAD. Underlining the key benefits resulting from the initiative,explaining the strategies and the development steps used toimplement it, and highlighting the main obstacles encountered andhow they were overcome will help repeat the experience in otheruseful e-government projects.Keywords—Case studies, Egypt, Electron